Radiologist Identification of Occult Dorsal Wrist Ganglion Cysts on MRI - Versteeg, Gregory; Goyal, Kanu (Journal of Wrist Surgery, 2019)
Background Occult dorsal ganglion cysts (ODGC) require imaging or an operation for detection. It is currently unknown how often a radiologist identifies an ODGC on magnetic resonance imaging (MRI) and whether surgeon indication for MRI aids the radiologist in detection.Questions/Purposes The aim of the study was to investigate the following questions: how accurately do radiologists identify ODGC on MRIs? What factors may be associated with missed ODGCs?Patients and Methods We retrospectively studied patients who underwent an operation for an ODGC and had a preoperative wrist MRI. Radiology report and surgeon's notes were evaluated to determine whether identification of the ODGC was noted and whether the surgeon indicated that the MRI was to evaluate for an ODGC. MRIs were reviewed, dimensions of cysts measured and volume of cyst calculated.Results Twenty-four patients and 25 MRIs were analyzed. The radiologist identified the ODGC in 19 cases (76%). Fifteen of the 25 MRIs (60%) ordered had ODGC listed in the requisition comment by the ordering surgeon. Thirteen of these 15 (87%) ODGCs were seen by the radiologist. Ten of the 25 MRIs (40%) ordered did not mention ODGC in the requisition. Six of these 10 (60%) ODGCs were seen by the radiologist. The volume of the ODGCs missed by radiologists was smaller (mean, 0.049 cm3) than those the radiologists identified (mean, 0.31 cm3; p = 0.004).Conclusions Radiologists will not always identify the ODGC on an MRI, but they were more likely to if the surgeon was concerned for one. Hand surgeons should report suspicion of an ODGC on MRI requisition and review all imaging independently.Level of Evidence This is a Level III, prognostic study.
Keywords: ganglion cyst; MRI; imaging; cyst; radiology